Effects of Delta-Like Noncanonical Notch Ligand 1 Expression of Human Fetal Liver Hepatoblasts on Hematopoietic Progenitors - Jörg C. Gerlach; Robert L. Thompson; Bruno Gridelli; Eva Schmelzer (Stem Cells International)
Although the hepatic and hematopoietic progenitors of the liver are well characterized, the interactions between these two lineages remain mostly elusive. Hepatoblasts express delta-like noncanonical Notch ligand 1 (Dlk1), whose cleaved extracellular domain can become a soluble protein. We assessed the effects of DLK1 gene expression knockdown in cultures of total fetal liver cells. Furthermore, we separated Dlk1+ hepatoblasts from the total liver cell fraction and investigated effects of direct cell contact. Dlk1- cells were cultured either without Dlk1+ hepatoblasts, in direct contact with hepatoblasts, or separated from hepatoblasts by a porous membrane in inserts to inhibit cell contact but allow free exchange of molecules. Expression of the hepatic and hematopoietic genes, colony forming unit potential of various hematopoietic progenitors, and cell numbers and types were investigated. We found that DLK1 knockdown in total fetal liver cell cultures decreased total cell numbers. The expression of hepatic progenitor genes and mature hematopoietic genes was affected. Hematopoietic BFU-E and CFU-GM colony numbers were reduced significantly. The depletion of Dlk1+ hepatoblasts in culture decreased the potential of all hematopoietic progenitors to form colonies of all types and reduced the percentage of mature hematopoietic cells. The addition of hepatoblasts in inserts to Dlk1- cells further decreased the potential to form the CFU-GM and CFU-GEMM colonies and the percentage of mature hematopoietic cells but increased total cell numbers. Conclusively, direct contact of Dlk1 supports hematopoietic progenitor expansion and functionality that cannot be reconstituted in coculture without direct cell contact.